Analisis Kinerja Anggota Satpol PP Kota Bekasi Dalam Penertiban Pedagang Kaki Lima di Kota Bekasi - Dewo Septian; Wahidin Septa Zahran; Renisya Ayu Utami (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The background of this research is the increasing number of stree vendors (PKL) in Bekasi City who are not orderly, causing negativ impacts due to misuse of the functions of public facilities an infrastructure and can reduce cleanliness, beauty, comfort and othe aesthetic factors. This study aims to analyze the performance o members of the Bekasi City SATPOL PP in Controlling Stree Vendors in Bekasi City. The researcher chose to use the wor measurement indicators put forward by Anwar Prabu Mangkunegar in his book entitled Enterprise Human Resource Management which includes 5 indicators. Namely Quality of Work, Quantity of Work Responsibility, Cooperation, and Initiative. This research uses descriptive research type using qualitative methods. The results of th study show that the performance of Bekasi City SATPOL PP members in controlling street vendors is quite good but not optimal because there are still several obstacles found in the implementation o controlling in the form of debates, blockades and intimidation